LEGAL ANALYSIS OF THE APPLICATION OF CONSUMER PROTECTION TO SPARE PARTS WARRANTY IN THE SALE AND PURCHASE OF HONDA MOTORCYCLES (STUDY IN CV. GRAHA HONDA MARTUBUNG) - Sugio Sugio; Maswandi Maswandi; Azwir Agus (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The growth of the automotive industry, particularly motorcycles in Indonesia, has driven an increase in sales and purchase transactions, where spare parts warranties are one of the important factors in consumer decision-making. However, uncertainties often arise regarding warranty implementation, leading to conflicts between sellers and buyers. This study aims to analyze the implementation of consumer protection related to spare parts warranties in motorcycle sales and purchase transactions at CV. Graha Honda Martubung, as well as identify inhibiting factors and applicable solutions. The research method used is empirical juridical with a descriptive analytical approach. Data was collected through library research and field research, including interviews with company representatives, consumers, and relevant legal experts. The results show that the implementation of spare parts warranties at CV. Graha Honda Martubung is largely in accordance with regulations, but there are several obstacles such as insufficient socialization to consumers regarding warranty terms, claim procedures that are still considered complicated, and limited stock of certain spare parts. Based on the analysis results, this study provides recommendations including increased socialization, simplification of claim procedures, and better stock management to improve services and consumer protection.